Nanoscience and nanoengineering of cement-based materials - Constantinides, Georgios (My University, 2013)
Concrete is the most widely used construction material and given the current population growth, economic development, and need for repair/replacement of aging infrastructure, its consumption is expected to increase. Unfortunately though, the production of one of its major constituents, cement, is associated with approximately 5-10% of the global anthropogenic carbon dioxide emissions and therefore the industry and the specific material is in urgent need for reevaluation. The chemical reactions and resulting products that are produced when cement is mixed with water create a material that is highly complex. The dominant component, C-S-H gel, has a local structure of a precipitate with nanoscale features that are difficult to model and understand. Consequently, the development of the material relied primarily on empirical knowledge obtained through macroscopic experimentation and little is known about the underlying mechanisms that control the response of the material when employed in engineering applications. Recent experimental and theoretical advancements in the field of nanoscience and nanotechnology provide optimistic expectations for a refined understanding of the material that will create the scientific basis for a more sustainable and eco-efficient construction.
Keywords: C-S-H nanomechanics; Concrete nanocomposites; Concrete nanoengineering; Concrete nanoscience